Accumulative Competitive Season Training Stress Affects Neuromuscular Function and Increases Injury Risk in Uninjured D1 Female Athletes - Purdom, Troy M.; Levers, Kyle S.; Giles, Jacob; Brown, Lindsey; McPherson, Chase S.; Howard, Jordan (Frontiers in Sports and Active Living, 2021)
Previous research has shown that acute competition training stress negatively affects neuromuscular function which can perpetuate a predisposition to injury. This study’s aim was to investigate the effect of accumulated competition training stress effect on neuromuscular function and incidence of increased injury risk in uninjured female D1 soccer players. Neuromuscular function was evaluated in fifteen female division I soccer athletes who played >85% of competitive season competitions who were tested for mobility/stability, leg length symmetry, and vertical power at three different points across the competitive season (pre, mid and post time blocks). Leg length symmetry was measured from the anterior superior iliac spine to the lateral malleolus prior to Y-balance testing. The Y-balance testing measures unilateral anterior, posteromedial, and posterolateral reach achieved in single leg stance using metrics that include L/R normalized composite reach (NCOMP), L/R normalized anterior reach (NANT), and L/R NCOMP/NANT segmental differences across time. Injury risk was evaluated using validated objective criteria that included: (NCOMP total reach <94% of limb length*3), (NANT reach distance <84% leg length) along with NCOMP and NANT asymmetries >4.0. Maximal vertical power (MVP) was measured via vertical jump. Multiple repeated measures ANOVAs evaluated NCOMP, NANT, MVP, and leg length symmetry across time with LSD post hoc testing when relevant (X+SD). A significant main effect was found (F1,14 = 62.92, p < 0.001; η2 =0.82) with training stress and neuromuscular function without affecting maximal vertical power. Eighty percent of subject’s bilateral NCOMP scores fell below the YBT reach standard at midseason (ES=0.95, p=0.02) while all subjects NANT reach distance remained below the reach threshold (ES=0.74, p=0.003) indicating a 6.5x and 2.5x greater injury risk, respectively. Competition stress affected neuromuscular function without affecting maximal power, which negatively impacted stability and increased injury risk.